2019
DOI: 10.3390/en12132599
|View full text |Cite
|
Sign up to set email alerts
|

Parametrization of a Modified Friedman Kinetic Method to Assess Vine Wood Pyrolysis Using Thermogravimetric Analysis

Abstract: Common kinetic parameters were obtained for leached and non-leached samples of vine wood biomass. Both samples were considered to have different proportions of cellulose, hemicellulose, and lignin compositions as a result of the leaching process. The two samples were analyzed in terms of pyrolysis kinetic parameters using non-isothermal thermogravimetric analysis. Furthermore, the classic Friedman isoconversional method, a deconvolution procedure using the Fraser–Suzuki function, and a modified Friedman method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
3
1
Order By: Relevance
“…The sunflower in the current work produced higher biochar yield and lower pyrolysis conversion rates compared to sunflower bagasse [43] and sunflower stalks [44], which were reported at 28% char yield at 520 • C, and 25% char yield at 540 • C, respectively. Vine rod in the current work showed higher char production rates at 500 • C compared to the work by Suárez et al [45] who produced 35% biochar rates at the same temperature, which significantly reduced to 20% when the biomass was leached with distilled water before pyrolysis.…”
Section: Mass Change During Pyrolysis Using Tgacontrasting
confidence: 49%
“…The sunflower in the current work produced higher biochar yield and lower pyrolysis conversion rates compared to sunflower bagasse [43] and sunflower stalks [44], which were reported at 28% char yield at 520 • C, and 25% char yield at 540 • C, respectively. Vine rod in the current work showed higher char production rates at 500 • C compared to the work by Suárez et al [45] who produced 35% biochar rates at the same temperature, which significantly reduced to 20% when the biomass was leached with distilled water before pyrolysis.…”
Section: Mass Change During Pyrolysis Using Tgacontrasting
confidence: 49%
“…The second and third stages, 23.86% and 44.00% of weight loss, respectively, are associated with the decomposition of the polyol stable segments 18,44,56 . The fourth stage corresponds to 11.36% of weight loss and it is related to the decomposition of residues into volatile compounds, occurring after 500°C 44,57 . In general, ISO addition increased the thermal stability, and the compound with 30% ISO presents the highest initial degradation temperature.…”
Section: Resultsmentioning
confidence: 98%
“…and it is related to the decomposition of residues into volatile compounds, occurring after 500 C. 44,57 In general, ISO addition increased the thermal stability, and the compound with 30% ISO presents the highest initial degradation temperature.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…As one of the most common techniques, thermogravimetric analysis (TGA) is usually used for biomass pyrolysis analysis. Numerous works on kinetic studies of wood have been reported in literature studies. , Various isoconversional methods such as Kissinger, Kissinger–Akahira–Sunose, Flynn–Wall–Ozawa (FWO), , Starink, and Friedman methods ,, were used to calculate the kinetic parameters, while the Criado method, the Avrami equation, , and the Coats–Redfern (CR) method were used to predict the reaction mechanism. It was found that the main mechanisms of wood were three-dimensional diffusion, random nucleation with one nucleus mechanisms, and reaction order (2nd to 3rd) …”
Section: Introductionmentioning
confidence: 99%